2015
DOI: 10.1007/s10995-015-1848-1
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Adverse Preconception Risk Factors Between Women with and Without Disabilities

Abstract: Objective The objective of this study was to compare the prevalence of select preconception health indicators among women with and without disabilities. Methods 2010 Behavioral Risk Factor Surveillance System data were used to estimate the prevalence of health behaviors, health status indicators, and preventive health care among non-pregnant women ages 18–44 years with (N=8,370) and without (N=48,036) disabilities. Crude percentages were compared with chi-square statistics. Multivariable logistic regressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 43 publications
1
45
1
5
Order By: Relevance
“…The resulting lack of clinicians’ knowledge puts WWPD at higher risk during pregnancy than women without disabilities. Many of these women are at higher risk for complications of pregnancy than other women because of complex health issues related to their disability (Iezzoni, Yu et al, 2014, 2015; Mitra et al, 2016a; Signore, Spong, Krotoski, Shinowara, & Blackwell, 2011). Although some of the issues identified by the women in this study may also occur in women without disabilities, the WWPD who participated specifically addressed the issues within the context of having a physical disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting lack of clinicians’ knowledge puts WWPD at higher risk during pregnancy than women without disabilities. Many of these women are at higher risk for complications of pregnancy than other women because of complex health issues related to their disability (Iezzoni, Yu et al, 2014, 2015; Mitra et al, 2016a; Signore, Spong, Krotoski, Shinowara, & Blackwell, 2011). Although some of the issues identified by the women in this study may also occur in women without disabilities, the WWPD who participated specifically addressed the issues within the context of having a physical disability.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the passage of the Americans with Disabilities Act 25 years ago, individuals with disabilities, including those with physical disabilities, continue to experience barriers to health care (Peacock, Iezzoni & Harkin, 2015); the negative effects of these barriers extend to pregnant women with physical disabilities. A growing body of research has demonstrated that women with disabilities have unmet needs and experience complications related to pregnancy and childbearing that are uncommon in women without disabilities (Iezzoni, Yu, Wint, Smeltzer, & Ecker, 2014, 2015; Mitra, Clements, Zhang, & Smith, 2016a; Mitra, Long-Bellil, Iezzoni, Smeltzer, & Smith, 2015). Women with physical disabilities (WWPD) reported negative attitudes toward them from acquaintances as well as strangers (Iezzoni, Wint, Smeltzer, & Ecker, 2015a; Nosek, Rintala, Howland, Foley, & Bennett, 1995).…”
mentioning
confidence: 99%
“…Women with disabilities during preconception and during pregnancy are more likely to self-report fair to poor health compared to those without disabilities. 59,60 For instance, delayed prenatal care may potentially have a greater impact on the health status of women with physical disabilities compared to women in the general population. In addition, other mediators unique to women with physical disabilities such as unmet needs for personal care assistance, inaccessible examination tables, and weighing scales may have an added impact on the health and functioning of women with disabilities and their infants.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other women, women with mobility disability have higher rates of comorbid and behavior-related health conditions that are pregnancy risk factors (Iezzoni, Yu, Wint, Smeltzer, & Ecker, 2014, 2015; Kim, Kim, Hong, & Fredriksen-Goldsen, 2013; Mitra et al, 2015; Mitra, Clements, Zhang, & Smith, 2016). They may also have higher rates of pregnancy complications, including pre-term birth (Mitra et al, 2015) and post-partum depression.…”
Section: Introductionmentioning
confidence: 99%
“…They may feel their obstetrical clinicians have inadequate knowledge or discriminatory attitudes about pregnancy among women with mobility disability (Mitra et al, 2016; Smeltzer, 2007). Finally, when in public while visibly pregnant, these women may confront perplexed comments, intrusive questions, or hostile responses from strangers (Iezzoni, Wint, Smeltzer, & Ecker, 2015b).…”
Section: Introductionmentioning
confidence: 99%